Science and the Stanislavsky tradition of acting - Pitches, Jonathan, 1968- (Routledge advances in theatre and performance studies, 2006)
Providing new insight into the well-known tradition of acting, Science and the Stanislavsky Tradition of Acting is the first book to contextualise the Stanislavsky tradition with reference to parallel developments in science. Rooted in practice, it presents an alternative perspective based on philosophy, physics, romantic science and theories of industrial management. Working from historical and archive material, as well as practical sources, Jonathan Pitches traces an evolutionary journey of actor training from the roots of the Russian tradition, Konstantin Stanislavsky, to.